Synthesis and rearrangements of aminosubstituted ferra- and ruthenatricarbaboranes - Holub, Josef; Grüner, Bohumír; Perekalin, Dmitry S; Golovanov, Denis G; Lyssenko, Konstantin A; Petrovskii, Pavel V; Kudinov, Alexander R; Stíbr, Bohumil (Inorganic chemistry, 2005)
A room-temperature reaction between the [7-tBuNH-nido-7,8,9-C3B8H10]- anion (1a) and [Cp*RuCl]4 leads to the ruthenatricarbollide [1-Cp*-12-tBuNH-1,2,4,12-RuC3B8H10] (2) (yield 85%). Analogously, the room-temperature photochemical reaction of 1a with [CpFe(C6H6)]PF6 gives the previously reported iron complex [1-Cp-12-tBuNH-1,2,4,12-FeC3B8H10] (3) (yield 82%). Both reactions are associated with extensive polyhedral rearrangement, which occurs under very mild conditions and brings the carbon atoms to positions of maximum separation within the framework. Compounds 2 and 3 were also surprisingly obtained via complexation of the isomeric [8-tBuNH-nido-7,8,9-C3B8H10]- (1b) anion. Complex 2 rearranges further to [1-Cp*-10-tBuNH-1,2,4,10-RuC3B8H10] (4) upon refluxing in xylene (145 degrees C). Density functional theory calculations at the B3LYP/SDD level were used to estimate relative stabilities of these metallacarborane isomers. Compounds 2 and 4, along with the 11-vertex closo compounds [1-Cp*-1,2,3,10-RuC3B7H10] (5) and [1-Cp*-10-tBuNH-1,2,3,10-RuC3B7H9] (6), were also isolated from the reaction between [Cp*RuCl2]2 and 1a in boiling xylene. The structure of 2 was established by an X-ray diffraction study, and the constitution of all compounds was determined unambiguously by multinuclear NMR spectroscopy, mass spectrometry, and elemental analyses.